Security vulnerabilities related to web-based data - Mohammed Awad; Muhammed Ali; Maen Takruri; Shereen Ismail (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
In this digital era, organizations and industries are moving towards replacing websites with web applications for many obvious reasons. With this transition towards web-based applications, organizations and industries find themselves surrounded by several threats and vulnerabilities. One of the largest concerns is keeping their infrastructure safe from attacks and misuse. Web security entails applying a set of procedures and practices, by applying several security principles at various layers to protect web servers, web users, and their surrounding environment. In this paper, we will discuss several attacks that may affect web-based applications namely: SQL injection attacks, cookie poisoning, cross-site scripting, and buffer overflow. Additionally, we will discuss detection and prevention methods from such attacks.